DMRT Transcription Factors in the Control of Nervous System Sexual Differentiation - Casado-Navarro, Rafael; Serrano-Saiz, Esther (Frontiers in Neuroanatomy, 2022)
Sexual phenotypic differences in the nervous system are one of the most prevalent features across the animal kingdom. The molecular mechanisms responsible for sexual dimorphism throughout metazoan nervous systems are extremely diverse, ranging from intrinsic cell autonomous mechanisms to gonad-dependent endocrine control of sexual traits, or even extrinsic environmental cues. In recent years, the DMRT ancient family of transcription factors has emerged as being central in the development of sex-specific differentiation in all animals in which they have been studied. In this review, we provide an overview of the function of Dmrt genes in nervous system sexual regulation from an evolutionary perspective.